Indigenous oil palm farmers in peninsular Malaysia: a collective enterprise approach to socioeconomic sustainability - Yew, Wong Chin; Azlizan Mat Enh; Azlina Abdullah; Nur Hafizah Yusoff; Sia, Mal Kong (Penerbit Universiti Kebangsaan Malaysia, 2023)
Growing oil palm among the indigenous peoples in Peninsular Malaysia is not uncommon. While individuals’ success either economically or academically are lauded and ought to be nurtured and supported, previous study by Wirth believes that collective success is the key not only in elevating the socioeconomic status but also serves as a mean to retain them as a cohesive unit culturally and socially. This study aims in promoting a model for collective development in the form of cooperative in oil palm cultivation of the indigenous peoples. Through simple random sampling and snowball techniques, a total of fifteen small-scale oil palm farmers from an indigenous village in the state of Pahang were interviewed periodically during the months of June till September, 2020. The results of the study found that these indigenous oil palm farmers faced both social and economic issues between the household members as well as within the indigenous community arising from inequalities of income level. At the macro level, a competent cooperative will attain far greater achievements and more beneficial to the indigenous community than a few successful farmers due to the concept of inclusiveness and sustainability. It is hope that the cooperative model can be replicated in other indigenous communities and effectively raise the overall living standard of the indigenous community in Peninsular Malaysia.